Globalization as Politics of Neo-Colonization: Teaching English language in Higher Education in Nepal - Sharma, Raj Kumar (Journal of NELTA Surkhet, 2018)
This article briefly discusses colonial history as background knowledge and then tries to define globalization covering some of the issues of globalization. Through defining and covering some issues regarding globalization, it enters into the issue of neo-colonization. After that, it gives a brief glimpse that how the teaching English language in higher education of Non-western has blended the politics of Neo-colonization.Journal of NELTA Surkhet,  Vol. 5 January, 2018, Page: 106-112